Peran Kepala Sekolah dalam Meningkatkan Profesionalisme Guru di SMP Negeri 1 Banyudono - Fatimah, Sanastri Dela; Azani, Mohammad Zakki (Cetta: Jurnal Ilmu Pendidikan, 2025)
Education is a lifelong learning activity, both at school and non-school levels. One of the influential in achieving educational goals is the principal. The principal is a leader who has a role to organize, manage, educate and lead in educational institutions. This study aims to describe the role of the principal in improving teacher professionalism at SMP Negeri 1 Banyudono, explaining the principal's strategy in improving teacher professionalism at SMP Negeri 1 Banyudono. In dealing with teacher professionalism, the principal of SMP Negeri 1 Banyudono said that there were still thoughts that were in the comfort zone even though the research method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study showed that the role of the principal at SMP Negeri 1 Banyudono was to manage school human resources, including educators and other education personnel. In improving teacher professionalism, the principal directed all educators to study independently through certain platforms in order to improve the quality of education in schools. The strategies used are to provide teachers with an understanding of the school's vision and mission, improve teacher competency through training activities, independent learning from various platforms, share good practices, make learning community activities in schools more effective, improve communication and collaboration, conduct observations, monitoring, supervision and evaluation, provide support and facilities, build a positive culture and provide motivation.